1973
DOI: 10.1063/1.1679712
|View full text |Cite
|
Sign up to set email alerts
|

Endothermic ion-molecule reactions in silane

Abstract: Endothermic ion-molecule reactions in silane are reported together with rate constants for the observed reactions. Si2+ is observed only from endothermic reactions of Si+ and SiH2+ with silane. Endothermic as well as exothermic channels are observed for the formation of Si2H+, Si2H2+, and Si2H3+. The kinetic energy dependence of reactions yielding Si2H+, Si2H2+, Si2H3+, and Si2H4+ products is reported and analyzed in terms of the mechanism and kinematics of fragmentation for the excited intermediate ion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Endothermic reactions of cations have been studied by Yu et al [65] and HENIS et al [69] in SiH4, by CHENC et al [66] in SizHB and by Allen et al [64] in H2. These reactions involve H atom elimination such as…”
Section: A T I O N -M O L E C U L E R E a C T I O N S Si H Y D R I mentioning
confidence: 99%
“…Endothermic reactions of cations have been studied by Yu et al [65] and HENIS et al [69] in SiH4, by CHENC et al [66] in SizHB and by Allen et al [64] in H2. These reactions involve H atom elimination such as…”
Section: A T I O N -M O L E C U L E R E a C T I O N S Si H Y D R I mentioning
confidence: 99%
“…1 the secondary ions, Si 2 H n + (n = 1-5), were observed and their formation was related to the SiH 2 + reactant ion. Subsequent studies [2][3][4][5][6] showed however that all the primary SiH n + (n = 0-3) ions react with SiH 4 and participate in processes leading to Si 2 -cations. Larger siliconhydrogen cluster ions were also observed 2 and subsequently investigated under various experimental conditions.…”
Section: Journal Of Mass Spectrometrymentioning
confidence: 99%
“…Larger siliconhydrogen cluster ions were also observed 2 and subsequently investigated under various experimental conditions. [7][8][9] the rate constants, the thermochemistry, and the mechanistic aspects of the ionic processes occurring in ionised SiH 4 have been discussed, in particular, in two series of benchmark experimental [10][11][12][13][14][15] and theoretical [16][17][18][19] studies. the ion chemistry occurring in SiH 4 -based mixtures has been also investigated with considerable interest (especially by Lambert and co-workers), [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] related also to the role of ionic species in the formation of electronic and optoelectronic materials by chemical vapour deposition techniques.…”
Section: Journal Of Mass Spectrometrymentioning
confidence: 99%
“…the chemically constrained clustering reactions that are observed for subsilane cations with pure silane and disilane. [11][12][13][14][15][16][17][18][19][20] In both silane and disilane, all cation clustering reactions lead to terminal cluster ions at quite small sizes where further growth stops. [14][15][16][17][18][19][20][21][22][23][24] The chemistry of small Six Dycluster anions with pure silane is less well known.…”
Section: Introductionmentioning
confidence: 99%